Myeloid-Derived Suppressor Cells in COVID-19: The Paradox of Good - Grassi, Germana; Notari, Stefania; Gili, Simona; Bordoni, Veronica; Casetti, Rita; Cimini, Eleonora; Tartaglia, Eleonora; Mariotti, Davide; Agrati, Chiara; Sacchi, Alessandra (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome-coronavirus (SARS-CoV-2) is the causative agent of the ongoing coronavirus disease 2019 (COVID-19) pandemic. Viral replication in the respiratory tract induces death of infected cells and release of pathogen- associated molecular patterns (PAMPs). PAMPs give rise to local inflammation, increasing secretion of pro- inflammatory cytokines and chemokines, which attract immune cells from the blood into the infected lung. In most individuals, lung recruited cells clear the infection, and the immune response retreats. However, in some cases a dysfunctional immune response occurs, which triggers a cytokine storm in the lung leading toacute respiratory distress syndrome (ARDS). Severe COVID-19 is characterized by an impaired innate and adaptive immune response and by a massive expansion of myeloid-derived suppressor cells (MDSC). MDSC function as protective regulators of the immune response, protecting the host from an over immune reactivity and hyper-inflammation. However, under some conditions, such as chronic inflammation and cancer, MDSC could exert a detrimental role. Accordingly, the early expansion of MDSC in COVID-19 is able to predict the fatal outcome of the infection. Here, we review recent data on MDSC during COVID-19, discussing how they can influence the course of the disease, and whether they could be considered as a biomarker and possible target for new therapeutic approaches.